Elucidating the microbial resuscitation cascade in biological soil crusts following a simulated rain event. (6th May 2013) - Angel, Roey; Conrad, Ralf
Summary Biological soil crusts (biocrusts) are photosynthetic mats formed through an association of prokaryotic and eukaryotic microorganisms with soil particles. Biocrusts are found in virtually any terrestrial ecosystem where vascular plant coverage is abiotically limited, with drylands comprising the primary habitat for them. We studied the dynamics of the active bacterial community in two biocrusts from an arid and a hyperarid region in the Negev Desert, Israel, under light‐oxic and dark‐anoxic incubation conditions after simulated rainfall. We used H218O for hydrating the crusts and analysed the bacterial community in the upper and lower parts of the biocrust using an RNA‐stable isotope probing approach coupled with 454‐pyrosequencing. In both biocrusts, two distinct bacterial communities developed under each incubation condition. The active anaerobic communities were initially dominated by members of the order Bacillales which were later replaced by Clostridiales. The aerobic communities on the other hand were dominated by Sphingobacteriales and several Alphaproteobacteria (Rhizobiales, Rhodobacterales, Rhodospirillales and Rubrobacteriales). Actinomycetales were the dominant bacterial order in the dry crusts but quickly collapsed and accounted for < 1% of the community by the end of the incubation. Our study shows that biocrusts host a diverse community whose members display complex interactions as they resuscitate from dormancy.